The situation of practical education in secondary educational institutions for teacher training in the middle of the last century (Training and Practice : Journal of Educational Sciences, 2018)
The objective of the investigation is to present and analyse the forms and the documents related to the regulation in practical training. In the course of the essay we will go into details concerning the difficulties and problems in organising practical training as well as the issue whether the vocational training allowed to contribute to develop trainee teachers’ expertise. The use of primary sources such as curricula and regulations were included during the investigation.